Ticks and tick-borne pathogens on Belle-Île-en-Mer: An exploratory study in a western French island environment - A. Haidar-Ahmad; C. Barthel; P. Boyer; G. Joncour; B. Degeilh; N. Boulanger (Ticks and Tick-Borne Diseases)
The islands of Brittany provide unique ecosystems for ticks and tick-borne diseases owing to their oceanic climate, influencing interactions among ticks, hosts, and pathogens. We conducted a preliminary investigation on Belle-Île-en-Mer, an island off the Atlantic coast of Brittany in western France, to assess the prevalence of questing adult ticks and associated human pathogenic bacteria. Dermacentor spp. were found to dominate the tick population (61 %): 23 % Dermacentor reticulatus and 77 % D. marginatus. Haemaphysalis punctata (27 %) was also prevalent on the island, and Ixodes ricinus (12 %) was detected for the first time on Belle-Île-en-Mer. Both Dermacentor species harbored either Rickettsia slovaca (24 %) or Rickettsia raoultii (20 %), whereas I. ricinus carried Borrelia burgdorferi sensu lato and Anaplasma phagocytophilum but not Borrelia miyamotoi or Neoehrlichia mikurensis. Detection of two potentially pathogenic species in the B. burgdorferi sensu lato complex, B. afzelii and B. lusitaniae, along with A. phagocytophilum underscores the current risk of Lyme borreliosis and anaplasmosis. The high prevalence of Rickettsia infection in Dermacentor indicates an additional risk of human rickettsioses.